Comparative analysis of machine-planted and manual-planted wheat on crop and water productivity, and profitability under system of wheat intensification management - Dass, Anchal; Kushwaha, H. L.; Sahoo, P. K.; Dhar, Shiva; Choudhary, Anil K.; Khura, Tapan K.; Babu, Subhash; Singh, Arjun; Mani, Indra; Kumar, Mukesh; Kumar, Rajeev; Yadav, Devideen (Frontiers in Sustainable Food Systems, 2023)
System of Wheat Intensification (SWI) that involves the manual planting (dibbling) of 2 seeds in each hill, with hills laid-out in a square pattern (20×20 cm), is a laborious task, requiring more time, manpower, energy, and monetary expenditure. Thus, the scientists’ team of Agricultural Engineers and Agronomists at ICAR-Indian Agricultural Research Institute, New Delhi, developed a single-row manual SWI-planter (SRMSWIP) to make SWI planting easier, faster and more economical. The SRMSWIP-planter was field-evaluated for wheat var. HD-2967 during winter season of 2015 -16 in a randomized complete block design thrice-replicated. The treatments (08) included (i) sowing with SRMSWIP using treated seeds (MSWIT); (ii) sowing with SRMSWIP using non-treated seed (MSWINT); (iii) manual sowing with SWI-management using treated seeds (MSWIT); (iv) manual sowing with SWI-management using non-treated seeds (MLSWINT); (v) recommended planting with SWI-management using treated seeds (RPSWIT); (vi) recommended planting with No-SWI management using non-treated seeds (RPNoSWIT); (vii) check-row with SWI-management using treated (CRSWIT), and (viii) check-row with SWI-management using non-treated seeds (CRSWINT). The SWI-management increased the grain yield by 0.61–1.52 t ha-1 with an overall average increase of 1.12 t ha-1 over control plots. The greatest increase ( 25%) in grain yield was with the mechanical seeder and seed treatment. Straw yield was however lower under SWI-management, Water productivity and production-efficiency were higher under SWI compared to conventional seed-drilling. Gross returns with SWI planting ranged between Rs.123,526/ha in MLSWINT to Rs. 139,210/ha in MSWIT against Rs. 117,113/ha in RPNoSWIT. However, SWI with manual sowing (MLSWIT & MLSWINT) increased the cost of cultivation (COC) by Rs. 9,623/ha over RPNoSWIT. This increase in COC was lowered to Rs. 5,475/ha by planting with SRMSWIP. Thus, SWI planting and management barring MLSWINT improved net return by Rs. 7615–16,372/ha over conventional planting without SWI-management. The B:C ratio in MSWIT and MSWINT was significantly higher than RPSWI. Monetary-efficiency (ME) was highest with MSWIT (Rs. 702/ha/day). Overall, the SRMSWIP-planter may facilitate the wheat sowing using SWI methods with more feasibility and economical viability. The promotion of this low-cost SRMSWIP-planter may prove as a boon in enhancing the adoptability of SWI-technology among wheat growers’ in of south-Asia.